Comparison of third-trimester indices in pregnant women with and without COVID-19 infection: A cross-sectional study (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: The third trimester represents a critical window in pregnancy when these hematologic changes could have the greatest impact. Therefore, understanding how coronavirus disease 2019 (COVID-19) infection influences blood profiles during this period is vital for clinical management and risk stratification. In Kenya, while national guidelines recommend laboratory evaluation, including complete blood count, c-reactive protein (CRP), lactate dehydrogenase (LDH), and coagulation profiles for pregnant women with suspected or confirmed COVID-19, there is a paucity of local data documenting these hematologic trends.Objective: To investigate hematologic profile differences between pregnant women in the third trimester with and without COVID-19 infection.Methods: A cross-sectional comparative study was employed to compare hematological parameters in pregnant women with and without   COVID-19 between May 1st and August 31st, 2021. We recruited 60 eligible patients from the Nairobi hospital using purposive sampling. We assessed the complete blood count, coagulation profile, lactate dehydrogenase, and C-reactive protein.Results: Pregnant women with COVID-19 had significantly higher levels of neutrophils, prothrombin time, CRP, and LDH compared to those without, with respective AORs of 9.50 (p